Dealing With Brain MRI Findings in Pediatric Patients With Endocrinological Conditions: Less Is More? - Baldo, Francesco; Marin, Maura; Murru, Flora Maria; Barbi, Egidio; Tornese, Gianluca (Frontiers in Endocrinology, 2022)
Neuroimaging is a key tool in the diagnostic process of various clinical conditions, especially in pediatric endocrinology. Thanks to continuous and remarkable technological developments, magnetic resonance imaging can precisely characterize numerous structural brain anomalies, including the pituitary gland and hypothalamus. Sometimes the use of radiological exams might become excessive and even disproportionate to the patients' medical needs, especially regarding the incidental findings, the so-called "incidentalomas". This unclarity is due to the absence of well-defined pediatric guidelines for managing and following these radiological findings. We review and summarize some indications on how to, and even if to, monitor these anomalies over time to avoid unnecessary, expensive, and time-consuming investigations and to encourage a more appropriate follow-up of brain MRI anomalies in the pediatric population with endocrinological conditions.